Students’ Difficulties in Reading Authentic English Text in Vocational High School - Cyntia Tri Arrifiana (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
English is an essential skill that helps vocational students prepare for employment in the world of work. Thus, the English taught in vocational schools should be more specific because it requires technical vocabulary and industry-related language relevant to their major. Reading is considered a fundamental skill that can increase their knowledge in the vocational context related to their vocational field (Widodo, 2015). Using authentic material in the classroom benefits students by exposing them to real language in real-life contexts. In a vocational context, authentic text refers to texts and tasks based on the content they want to learn (Widodo, 2016). Reading materials such as advertisements, magazines, newspapers, articles, and literature are suitable for improving students’ reading ability and knowledge. However, these texts are often challenging for students to read and comprehend. According to the Program for International Student Assessment (PISA) survey in 2022, Indonesian students’ proficiency levels in reading performance are still low (Haryunianti & Suranto, 2021). Nuttall (1982) suggests that students must be proficient in five reading aspects, such as determining the main idea, locating references, making inferences, finding detailed information, and understanding the meaning of words provided in the text. This research used a descriptive qualitative research design. It was conducted in one of the vocational high schools in Jember. This school was chosen because it applies the EVP (English Vocational Purpose) approach in teaching English. Authentic text is used as the material of a reading test adapted to match students’ level of difficulty. After the reading test, an interview was conducted to gather indepth information on the cause of students’ difficulties in reading comprehension. The reading test was analyzed using basic percentages to find the students’ correctness in answering the questions. Furthermore, the interview was analyzed using thematic analysis by Braun and Clarke (2016). Based on the results of this research, the aspect of reading comprehension that students had the most difficulty with was determining the main idea, as indicated by the percentage of students’ answers in the reading test. In addition, the interview results described students’ difficulties in reading authentic English text. This research could hopefully provide valuable information for English teachers and future researchers. The teacher should develop a teaching strategy for training students’ reading comprehension in determining the main idea, especially in reading authentic English texts. Meanwhile, future researchers interested in the same topic can conduct their research with a different focus.
Reuploud file repositori 10 maret 2026_Firli
Keywords: Teaching Reading; Authentic English; Vocational High School